Condilomatosis en gestantes adolescentes que acudieron a la consulta externa en el hospital Dr. Nicolás Cotto Infante de la ciudad de Vinces en el periodo del 1 de septiembre del 2010 al 31 de marzo del 2011 - León Rivera, Karen Elizabeth (2011)
The persistent presence of HPV virus is the main factor for the development of uterine cervical cancer, studies have shown that this type of diseases are a gradual progression and their precursor lesions can be kept in reversible phase or in situ for several years; cervical cancer being the end of a set of epithelial disturbances Stadium; It is important to identify the infecting virus in premalignant lesions and even cervical processes where still not occur morphological changes associated with infection. In the Cotto Dr. Nicholas Hospital of the city of Vinces is recorded between the years 2010 and 2011: 21 cases of HPV of which 9 are adolescents amounting to 43 per cent which was not search if there was any Dysplasia, mild, moderate and or severe; as noted in the medical histories that were revised….